Sport Community Involvement and Life Satisfaction During COVID-19: A Moderated Mediation of Psychological Capital by Distress and Generation Z - Park, Juho; Uhm, Jun-Phil; Kim, Sanghoon; Kim, Minjung; Sato, Shintaro; Lee, Hyun-Woo (Frontiers in Psychology, 2022)
How can sport community involvement influence life satisfaction during a pandemic? Self-expansion theory posits that individuals seek to gain resources such as positive interpersonal relationships for growth and achievement. By considering psychological capital (PsyCap) as a dispositional resource intervening between sport community involvement and life satisfaction, we examined an empirical model to test the chain of effects. Based on the stress process model, distress and generational group (Generation Z vs. others) were tested as moderators. Participants (N = 233) responded to the scale item questionnaire for model assessment. Supporting the hypothesized relationships, the model was supported with a significant moderated-moderated mediation. The mediation effect of PsyCap was stronger when distress level was lower and such interaction effect was amplified for Generation Z (Gen Z). Whereas the global sport communities and Gen Z were found to be more particularly vulnerable to COVID-19, our findings suggest that there are psychological pathways for fans to maintain their resilience. It is foremost imperative to lower the stress level of sport fans for their community involvement to positively affect life satisfaction. Gen Z were more stressed during the pandemic but individuals who managed to cope with stress were able to leverage community involvement to boost positive psychological resources. Acknowledgment of these effects brings implications for better management strategies and provides avenues for new research.